Effect of Brand Experience on Brand Loyalty: The Mediating Role of Brand Satisfaction, Brand Trust, and Brand Commitment - Rizaldi, Novia; Thabrani, Gesit (Jurnal Economic Resource, 2025)
This study investigates the influence of brand experience on brand loyalty, with brand satisfaction, brand trust, and brand commitment serving as mediating variables. Focusing on users of Maxim, an online transportation service provider in Padang City, Indonesia, this research aims to explore how brand experience shapes customer loyalty both directly and indirectly. The study employed a convenience sampling method and collected data from 180 respondents. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS version 4.1.1.4. The results indicate that brand experience has a significant positive impact on brand satisfaction, trust, and commitment. Moreover, brand experience has a direct influence on brand loyalty. The findings also show that brand satisfaction and brand trust significantly mediate the relationship between brand experience and brand loyalty, while brand commitment does not exhibit a significant mediating role. These results offer practical implications for transportation service providers, such as Maxim, highlighting the importance of enhancing customer experience to strengthen satisfaction and trust. Theoretically, the study contributes to the literature on consumer behavior by validating the mediating roles of satisfaction and trust and identifying the limited impact of brand commitment in this service context.